Scientists and engineers in convergence technologies in Korea: where are they going and how do they collaborate? - Lee, Jungmann; Om, Kiyong; Choi, Minseok; Song, Chanhoo; Kim, Kwanyoung (Technological and Economic Development of Economy, 2014)
Today convergence technologies have become a major issue in science policy. This paper describes the current state of scientific collaboration in convergence technologies among researchers in South Korea, by conducting survey and the Social Network Analysis (SNA) with a data set of 1,095 researchers who have involved in the development of the convergence technologies. The main research findings are fivefold. First, dominant numbers of researchers are involved in convergence technology with IT because IT is recognized as the most competitive technology in Korea. Second, mobility of researchers is active in convergence technologies. Third, it is found that the researchers in convergence technologies are more productive in terms of the number of research papers per capita than those in other scientific fields. Fourth, they, however, show limited research collaboration, compared with their high productivity. Finally, the members of the network in convergence technologies are closer to each other than those in other scientific fields, but most of their collaborative relationships remain bilateral rather than triangular. Only a few researchers act as hubs, revealing that collaborative research relationship in convergence technologies in Korea is highly concentrated. At the last part, some policy recommendations to promote research collaboration in convergence technologies are discussed.